STRATEGI PEMASARAN PT.EIGERINDO MELALUI E-COMMERCE TERHADAP KEPUTUSAN PEMBELIAN - Nellya ningsih; Chomsun Farochi; Rahmat Hidayat (Jurnal Akrab Juara, 2019)
The marketing strategy is defined as the analysis of the development and implementation of the strategy in the strategy of determining the target market for the products in each business unit, marketing goal setting, and the development, implementation, and management of the marketing program strategy, positioning the market designed to meet consumer desires target markets. One of them with the use of information systems in the product marketing activities. One of them promote it through e-commerce. Which can make consumers in deciding to make a purchase decision for these products. This research was conducted in PT.Eigerindo. Before knowing the effect of E-Commerce on purchasing decisions, the normality test. Normality test result is normal, because the sig of 0.200> 0.05 (alpha). Furthermore, using ANOVA test. Results obtained from ANOVA test F value of 111.554, while F tables can be viewed using the f table with residual degrees of freedom (df) of 98 as a denominator and df regression is 3.94. Because the F count (111.554)> F table (3.94) then H1 accepted. Based on the significance, visible column sig is 0,000 that means the probability of 0,000 <0.05 then H0 is accepted